A aplicação do seguro de crédito interno no mercado brasileiro - Pereira, Angélica Pinheiro de Melo (2019)
Trade credit insurance has as its main objective to cover losses caused by the customer's default on sales within the country. It is a credit risk management tool by which companies can transfer their risks to insurers. Created in Brazil in 1957, it is observed that the product nowadays still has an incipient market when compared to other insurance lines. Thus, this paper aimed to research the domestic trade credit insurance market in Brazil, seeking to identify the reasons why the product does not develop in the country. The methodology of the work was the use of two descriptive research using survey. Data collection used two questionnaires, one for companies with multiple choice closed questions and one open question, and the second for the insurance market, with closed questions using the five-point Likert scale and one question using multiple choice. Basic descriptive and multivariate statistics were used to analyze the data. The results found through research aimed at companies reveal that the trade credit insurance market in Brazil is still underdeveloped and the adherence among contractors of the product is higher among foreign capital companies. Among the main motivations of companies regarding the hiring of trade credit insurance, it was found that for companies that do not contract are stand out the perception of low credit risk, information asymmetry, adverse selection and lack of knowledge about the product, for companies that stopped hiring are information asymmetry, moral hazard and process complexity, while for companies that hire are risk perception and the use of internal credit insurance for its management, and instruction of corporate headquarter. The results found in the research aimed at the insurance market revealed that of actions promoted by the insurers, the promotion of events to spread knowledge and promote credit insurance has the lowest emphasis, already of the characteristics of the Brazilian market, the lack of product knowledge and transparency in financial information are the characteristics that more difficult the development of trade credit insurance. This paper has practical implications for companies and the insurance market because it exposes several issues raised by credit and collection professionals in their analysis of trade credit insurance, and by insurance market professionals about the actions taken to develop the product in Brazil, and the particularities of the Brazilian market that difficult or not contribute to the growth of trade credit insurance in Brazil. The issues explored in this paper help identify the factors that hinder the development of domestic credit insurance in Brazil. Your contribution can help the insurance market to act more assertively promoting actions for the product development in the country and also for companies that can start to analyze trade credit insurance more deeply considering it in their processes as another credit risk management tool.